2014
DOI: 10.1186/s12245-014-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of South American physicians hosting foreign rotators in emergency medicine

Abstract: BackgroundEmergency Medicine (EM) is increasingly becoming an international field. The number of fellowships in International EM in the USA is growing along with opportunities to complete international health electives (IHEs) during residency training. The impact on host institutions, however, has not been adequately investigated. The objective of this study is to assess the experience of several South American hospitals hosting foreign EM residents completing IHEs.MethodsAnonymous, semi-structured one-on-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…While a majority of the literature focuses on benefits to resident education, hosting institutions also receive benefit from international exchanges. O’Donnell et al ( 2014 ) found that hosting institutions for international residents found improvement in knowledge sharing, transfer of medical knowledge, and formation of long-term relationships (Lukolyo et al 2015 ). These benefits were most pronounced when the residents were toward the end of their training and focusing on their future practice and research goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a majority of the literature focuses on benefits to resident education, hosting institutions also receive benefit from international exchanges. O’Donnell et al ( 2014 ) found that hosting institutions for international residents found improvement in knowledge sharing, transfer of medical knowledge, and formation of long-term relationships (Lukolyo et al 2015 ). These benefits were most pronounced when the residents were toward the end of their training and focusing on their future practice and research goals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mutual benefits, trainees do pose some challenges to host institutions including decreased efficiency and negative perceptions of hosting countries held by trainees. These and other challenges can be minimized by preparing residents prior to arrival to a host institution with education on medical, ethical, and cultural challenges that may be encountered during international experiences (O’Donnell et al 2014 ; Kraeker and Chandler 2013 ; Howe et al 2013 ). Overall, these collaborations and partnerships are gateways to facilitate cross-cultural information exchange and enhance worldwide quality of care (Shrime et al 2015 ; Klaristenfeld et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) remain in country long enough to integrate into the environment, and develop a working knowledge of the local system, pathology, and surgical procedures; and (3) cultivate flexibility, particularly in recognizing that despite their training, they will not be local experts 57 . As one LMIC surgeon notes, "…you should not seek to learn how to practice medicine, but instead learn how medicine is practiced in another country" 58 .…”
Section: Discussionmentioning
confidence: 99%
“…There are many putative concerns in sending US trainees overseas, including the potential economic effects at the host site, lack of reciprocity, language barriers, safety, and potential lack of supervision. 36 A future comprehensive survey of international partners in anesthesiology programs may clarify these questions.…”
Section: Discussionmentioning
confidence: 99%